Análise do grau de maturidade das práticas environmental, social and governance em empresas do setor de energia renovável - Pauline de Lima Sagrilo (2025)
Sustainability has become indispensable in the decision-making processes of global organizations, and the business model based on ESG (Environmental, Social, and Governance) practices is expanding, gaining prominence among stakeholders. These practices encompass issues such as climate change, human rights, diversity, and compensation policies. To assess their reliability, mechanisms that measure the maturity of ESG practices are used. In the renewable energy sector, these practices are especially relevant because, despite contributing to greenhouse gas emissions, they are fundamental to economic development. Thus, this study aimed to develop an ESG maturity framework for companies in the renewable energy sector. The research began with Systematic Literature Reviews to identify methods for integrating ESG into business models, ESG practices adopted by companies, and maturity scales for assessing these practices. The next steps included conducting a Fuzzy Delphi study with experts to validate the ESG practices best suited to the sector, followed by a survey applied directly to the energy sector, and the application of the Fuzzy Topsis method to rank the studied practices and develop an ESG maturity framework. The main results include a ranking composed of 37 practices considered to have medium to very high applicability in the renewable energy sector, as well as a maturity framework with the five main practices for each stage.